2011
DOI: 10.1021/jz200265w
|View full text |Cite
|
Sign up to set email alerts
|

Work-Function Engineering of Graphene Electrodes by Self-Assembled Monolayers for High-Performance Organic Field-Effect Transistors

Abstract: We have devised a method to optimize the performance of organic field-effect transistors (OFETs) by controlling the work functions of graphene electrodes by functionalizing the surface of SiO2 substrates with self-assembled monolayers (SAMs). The electron-donating NH2-terminated SAMs induce strong n-doping in graphene, whereas the CH3-terminated SAMs neutralize the p-doping induced by SiO2 substrates, resulting in considerable changes in the work functions of graphene electrodes. This approach was successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(131 citation statements)
references
References 29 publications
3
128
0
Order By: Relevance
“…Abundant results have shown that large E F shift of graphene from its E D could be realized by surface doping depending on the electron affinity and coverage of the surface adsorbate [44,45]. Change of graphene charge carrier concentration (electron or hole) due to the surface doping has been detected [38].…”
Section: Resultsmentioning
confidence: 99%
“…Abundant results have shown that large E F shift of graphene from its E D could be realized by surface doping depending on the electron affinity and coverage of the surface adsorbate [44,45]. Change of graphene charge carrier concentration (electron or hole) due to the surface doping has been detected [38].…”
Section: Resultsmentioning
confidence: 99%
“…3d), for example, -NH 2 decreases w m , whereas -F and -CN increase w m [66]. Note that the effects of increasing/decreasing w m are similar when casting the same SAM on different metals, for example, Au, Ag [54,67,68], Cu [69], Pt [70], ITO [71], and so on, as well as on nonmetal contacts (e.g., graphene) [72].…”
Section: Improving Injection Via Self-assembled Monolayer Dipole Formmentioning
confidence: 97%
“…oxidized moieties such as in GO) generates a band gap, opening its applicability in functional nanoelectronic devices. [24,25] The quenching of the fluorescence emission with the increment of the oxidation degree is related with the increase of the density of localized states that, as for the semiconductor, can force the dissipation energy processes toward non radiative paths (e.g. vibrational relaxation).…”
Section: Go Suspension Characterization (Different Oxidation Time)mentioning
confidence: 99%